miR-223 inhibits pulmonary lesions of rats with pulmonary tuberculosis - TONG Xiao-wei, XIAO Han (Jichu yixue yu linchuang, 2022)
Objective To explore the effect of miR-223 on pulmonary lesions and IFN-γ in rats with pulmonary tuberculosis(PT) mechanism of protein expression. Methods Rats were divided into normal group (NC group), pulmonary tuberculosis rat model group (PT group) and pulmonary tuberculosis rat model transfected with miR-223 mimics group (miR-223 group) with 10 in each group. T cells in peripheral blood was quantified by flow cytometry, IFN-γ in serum was detected by ELISA and IL-18 levels, and the number of Mycobacterium tuberculosis colonies was counted; the pathological changes of lung tissue were micros copied by HE staining; IFN-γ in lung tissue was detected by immunohistochemistry method; RT-qPCR was used to detect miR-223 mRNA and IFN-γ in lung tissue MRNA expression. Results In PT group, the peripheral blood T cell subsets were disordered, the level of CD3+,CD4+% significantly decreased, and CD8+% was increased (P＜0.05); CD3+ and CD4+ percentage in miR-223 group were higher than those in PT group, while the percentage of CD8+ was lower(P＜0.05). Serum IFN-γ and IL-18 in PT group increased(P＜0.05); the number of Mycobacterium tuberculosis colonies in PT group was more than that in NC group (P＜0.05); the colony number of Mycobacterium tuberculosis in miR-223 group was significantly less than that in PT group (P＜0.05). Total IFN-γ level in PT group was higher than that in NC group(P＜0.05) but was significantly inhibited in miR-223 group(P＜0.05). Conclusions miR-223 can inhibit the pulmonary inflammatory response caused by Mycobacterium tuberculosis, and miR-223 showed an effect of anti-tuberculosis bacteria and may regulate host immunity, so and can effectively inhibit the expression of IFN-γ in lung tissue and thus alleviates severity of tuberculosis.